Výuka účetnictví na středních školách - Pincová, Marie (Jihočeská univerzita, 2017)
Bakalářská práce se zabývá výukou účetnictví na středních školách, zejména na obchodních akademiích. Cílem je zjistit, jaké metody jsou dle učitelů nejefektivnější při výuce účetnictví a na základě výsledků navrhnout optimální způsob výuky. Práce je rozdělena na část teoretickou a praktickou. V první části jsou popsána teoretická východiska z pohledu výchovně vzdělávacího procesu, a to zejména dosažení efektivnosti didaktického procesu správným využitím didaktických prostředků se zaměřením na didaktiku účetnictví. V praktické části jsou stanoveny výzkumné otázky, je proveden smíšený výzkum s důrazem na kvantitativní výzkum formou dotazníkového šetření mezi učiteli účetnictví a žáky na obchodních akademiích v České republice a následně jsou vyhodnoceny výsledky a vyvozeny závěry a doporučení. Mezi hlavní problémy patří zejména požadavek na vyšší hodinovou dotaci a menší skupiny žáků ve třídě při výuce účetnictví.
Methodology of teaching accounting at secondary schools
Keywords: This thesis deals with teaching accounting at secondary schools; especially business academies. The aim is to find out the most effective teaching methods for accounting classes. The optimal method of teaching is suggested based on the teachers' survey results. This bachelor thesis is divided into two parts: theoretical and practical. The first part describes the theoretical background of the educational process. The focus is on achieving efficiency in a didactic process by using correct teaching methods suitable for accounting lectures. The questionnaire topics are defined in the practical part. Mixed survey research is conducted with emphasis on quantitative part of survey. The survey respondents were accounting teachers and students of business academies in the Czech Republic. At the end the survey results are evaluated and conclusions and recommendations are summarized. The main problems are insufficient study hours and big number of students per accounting class.; didactic system; didactics of accounting; application of didactic principles; organizational forms; teaching methods; didactic techniques; teaching aids; didactic interaction teacher - pupils